Akar Kebudayaan Barat - Hamid Fahmy Zarkasyi (Universitas Darussalam Gontor, 2013)
In tracking down the cultural history owned by civilliation, it is important to conduct research based on worldview perspective. Because every society scientifi activity will create their own worldview. The wordview that built above these scientific elements will construct their cultures. Worldview is certainly may not formed by it self. It will match, get acquinted, and assimilated with worldviews of many other civilizations.This theory approved by many scholars as structure determined birth of cultures of any civilizations, including the West. West culture on its birth and development also relies on Western Worldview. Western Worldview turned out in their history related very intense with Islamic Worldview which manifestated in the constructs of civilization that also covers therein culture concepts. Islamic Worldview gives a great influence on construct of Western Worldview.Including concepts of Western culture.